Fecal calprotectin and microbiota of the gut - V. G. Gorokhova (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Analysis of the literature and our research showed that an imbalance of the intestinal microbiota is associated with many diseases. We present some of the mechanisms of disease. Using non-invasive, simple, affordable method of determination of fecal calprotectin reveals the presence and progression of chronic non-specific inflammatory bowel disease, and can be widely used in clinical practice